Proof of concept: Effect of GLP-1 agonist on food hedonic responses and taste sensitivity in poor controlled type 2 diabetic patients. Issue 4 (July 2019) - Brindisi, Marie-Claude; Brondel, Laurent; Meillon, Sophie; Barthet, Sophie; Grall, Sylvie; Fenech, Claire; Liénard, Fabienne; Schlich, Pascal; Astruc, Karine; Mouillot, Thomas; Jacquin-Piques, Agnès; Leloup, Corinne; et al.
Abstract: Aims: GLP-1 analogues decrease food intake and have great promise for the fight against obesity. Little is known about their effects on food hedonic sensations and taste perception in poor controlled patients with type 2 diabetes (T2D). Materials and methods: Eighteen T2D patients with BMI ≥25 kg/m 2 and poor controlled glycemia were studied before and after 3 months of treatment with Liraglutide. Detection thresholds for salty, sweet and bitter tastes, optimal preferences, olfactory liking, wanting and recalled liking for several food items were assessed. Subjects also answered questionnaires to measure their attitudes to food. Results: T2D patients had a significant decrease in bodyweight and HbA1c after treatment with Liraglutide. Liraglutide improved gustative detection threshold of sweet flavors, and decreased wanting for sweet foods and recalled liking for fatty foods. It also led to a decrease in feelings of hunger. Conclusions: Liraglutide increases sensitivity to sweet tastes and decreases pleasure responses for fatty foods in poor controlled T2D patients, and is of particular interest in the understanding of the mechanisms of weight loss. Clinical trial: NCT02674893.